GERAKAN ZAKAT DI KOTA METRO (IMPLENTASI DAN PENGARUHNYA TERHADAP PEMBERDAYAAN UMAT) - Siti Zulaikha (Institut Agama Islam Negeri Metro, 2015)
This paper aims to determine the implementation of Law No. 23 of 2011 on the Management of Zakat by Bazda (Badan Amil Zakat Local) Metro City and its influence on society. And aims to determine the contributing factors; inhibiting the movement of charity in the city Metro. This paper is descriptive qualitative data collection using the techniques of observation, in-depth interviews (depth interview) with the life history of various actors in the community. This paper also uses participatory action research in order to obtain accurate data relating to zakat and performed well Focus Group discussion. Data analysis techniques using qualitative analysis and induction yaang analysis was used to analyze the legal system of zakat and social reality in the public notice on the implementation of zakat. Based on the results of the research, that the issuance of Law No. 23 of 2011 on the Management of Zakat affect the fulfillment of zakat in Metro City are becoming more organized and in accordance with the purpose of compulsory zakat. As a key enabler of charity movement activities in Metro City is the positive response of the Mayor with the additional rules to respond to the performance of Act No. 23 of 2011 on the Management of Zakat. Source zakat collected Metro City has been perceived by society such as; house renovation, scholarships, provision of means of places of worship. Inhibiting factor is understanding people in just the tithe, so zakat mal still less become a major breakthrough. Then further inhibiting factor is the lack of motivation of people to channel funds through the zakat BAZNAS Metro City.